2019
DOI: 10.1021/acsanm.9b01482
|View full text |Cite
|
Sign up to set email alerts
|

Halloysite-Doped Zinc Oxide for Enhanced Sunscreening Performance

Abstract: Halloysite (Hal) has already been proposed as a support for zinc oxide nanoparticles synthesis due to the possibility of adsorbing ZnO on its internal and external tubular surface, but no attention has been devoted to evaluate the effect of this support on radiation screening capabilities. In this paper, zinc oxide nanoparticles were obtained by three different methods in the presence of Hal. Adsorption, solvent evaporation, and solvothermal methods were used. Quantitative Zn was determined by inductively coup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…[ 32 ] Furthermore, the work from the Toyota Research and Development group shown definite and limelight effect of nanoclays (general nanoparticle) in polyamide‐6 resin. [ 33 ] Graphene (G), carbon nanoribbon, multiwalled carbon nanotubes (MWCNT), graphene oxide (GO), and nanoclays consist of nanotubes made from halloysite [ 34,35 ] create the recent document of generally utilized nanoparticles. [ 21 ] Hence, the industries and scientists are in continuous quest of designing multipurpose, robust, and cost‐efficient nanocomposites for developed, especially for various thermomechanical systems such as sensors, aerospace, conductors, automobile, conductors, petroleum processing facilities, aerospace, and any other advanced material applications.…”
Section: Introductionmentioning
confidence: 99%
“…[ 32 ] Furthermore, the work from the Toyota Research and Development group shown definite and limelight effect of nanoclays (general nanoparticle) in polyamide‐6 resin. [ 33 ] Graphene (G), carbon nanoribbon, multiwalled carbon nanotubes (MWCNT), graphene oxide (GO), and nanoclays consist of nanotubes made from halloysite [ 34,35 ] create the recent document of generally utilized nanoparticles. [ 21 ] Hence, the industries and scientists are in continuous quest of designing multipurpose, robust, and cost‐efficient nanocomposites for developed, especially for various thermomechanical systems such as sensors, aerospace, conductors, automobile, conductors, petroleum processing facilities, aerospace, and any other advanced material applications.…”
Section: Introductionmentioning
confidence: 99%
“…coalescence, with subsequent modification and beginning of the phase separation at 70 °C. As a natural product exhibiting amino acid characteristics, MAAs are sensitive to temperature increase (denaturation) and might start exhibiting instability from 50 °C 20,19 . Thus, this emulsion must not be exposed to a temperature of ≥ 50 °C, which could inactivate the active principle of these coatings.…”
Section: Resultsmentioning
confidence: 99%
“…Aguzzi et al evaluated the effect of ZnONPs on HNTs for photoprotection application focusing attention on the radiation screening capabilities of the material [ 56 ]. The authors investigated different synthetic approaches to obtaining ZnONPs on HNTs and correlated the synthetic method with the adsorption capacity of the obtained materials.…”
Section: Supramolecular Functionalizationmentioning
confidence: 99%